2009
DOI: 10.1002/etc.19
|View full text |Cite
|
Sign up to set email alerts
|

Binding of ciprofloxacin by humic substances: A molecular dynamics study

Abstract: A comprehensive assessment of the potential impacts of antimicrobials released into the environment requires an understanding of their sequestration by natural particles. Of particular interest are the strong interactions of antimicrobials with natural organic matter (NOM), which are believed to reduce their bioavailability, retard their abiotic and biotic degradation, and facilitate their persistence in soils and aquatic sediments. Molecular dynamics (MD) relaxation studies of a widely used fluoroquinolone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 54 publications
2
54
0
Order By: Relevance
“…Interestingly, the hydrophilic character, porosity and surface area of a DOM molecule was increased upon insertion of fully hydrated cations such as Na + and Ca 2+ , indicating a structure relaxation upon deprotonation (Sutton et al, 2005). Complexation of metal cations appeared to impede binding of xenobiotic anions but enabled outersphere ternary xenobiotic-metal-HS complexes (Aristilde and Sposito, 2010). Molecular mechanics calculation of organo-mineral associations revealed that hydrogen-bonding of humic substances to the mineral sites is subordinate, while metal-cation-bridges (Fe 3+ , Al 3+ ) dominated (Schulten and Schnitzer, 1997).…”
Section: Structural Informationmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, the hydrophilic character, porosity and surface area of a DOM molecule was increased upon insertion of fully hydrated cations such as Na + and Ca 2+ , indicating a structure relaxation upon deprotonation (Sutton et al, 2005). Complexation of metal cations appeared to impede binding of xenobiotic anions but enabled outersphere ternary xenobiotic-metal-HS complexes (Aristilde and Sposito, 2010). Molecular mechanics calculation of organo-mineral associations revealed that hydrogen-bonding of humic substances to the mineral sites is subordinate, while metal-cation-bridges (Fe 3+ , Al 3+ ) dominated (Schulten and Schnitzer, 1997).…”
Section: Structural Informationmentioning
confidence: 94%
“…Alternatively, this technical problem is overcome selecting an alternative force field. Recently model calculations were done using semiempirical quantum mechanics calculations by the complete neglect of differential overlap (CNDO) method (Pople and Beveridge, 1970) or employing molecular dynamics with the COMPASS force field, thus widening the applicability of the large humic-molecules to dynamic studies including ionic species (Aristilde and Sposito, 2010;Schulten and Leinweber, 2000;Sutton et al, 2005). 4.…”
Section: Potential and Open Questionsmentioning
confidence: 99%
“…The high mass load of the fluoroquinolones in the dewatered sludge resulted from the long-term cycling and accumulation of the fluoroquinolones during activated sludge treatment, due to the strong adsorption of fluoroquinolones. The solubilities of fluoroquinolones are low (Table S1) and they can interact strongly with clay, nature organic matter and metal oxides (Aristilde and Sposito, 2010;Pei et al, 2010) (Table S1). It is obvious that adsorption onto sludge is an important aqueous phase removal mechanism for the fluoroquinolones in a WWTP.…”
Section: Removal Mechanismsmentioning
confidence: 99%
“…), much weaker polar interactions between the uncharged regions of the FQs and HA can also take place, such as H bonding (e.g. between the FQ-dissociated carboxyl and a HA-protonated amino group) or Van der Waals (Aristilde and Sposito 2010;Pignatello 2011).…”
Section: Resultsmentioning
confidence: 99%